PELAYANAN PUBLIK PADA PUSAT KESEHATAN MASYARAKAT KECAMATAN MARPOYAN DAMAI PEKANBARU TAHUN 2013 - Asrida, Wan; Puspita Pohan, Rafni (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
Public Services of Public Health Centers at the Sub District MarpoyanDamai in the City of Pekanbaru year 2013-2014. Purpose of this study was todetermine the Public Services in Public Health Centers at the District MarpoyanDamai in City of Pekanbaru and what are the factors that obstruct the services. Thisresearch used qualitative methods, research that provides an explanation of data isdone through the process of preparation, presentation of data, observation, interviewtechniques, and Documentation. The result of this research. concluded that the PublicService is still not optimal given employee health centers. Can be seen from thestandard indicators of public services according to kepmenpan No. 63 of 2003,service procedures are difficult, long turnaround time of service, limited serviceproducts, facilities and infrastructure is not yet complete, and then the employeecompetence of Health Centre, who do not show a friendly attitude to patients.Keywords : Public Services, Obstruction Factors, Public Health Center (PHC)